Artist occupation: Isaac Felipe Azofeifa - Alvarado Retana, Jeannette (2016)
The following work is intended to show Isaac Felipe Azofeifa as the dreaming, transgressive character who broke paradigms through time and space, daring to imagine that things could be different and inviting us to revisit with our human essence. His work was not only influential during his lifetime, but even in his physical absence his spell is still fluttering inside us, subtly hidden and making us more sensitive to change and self-organization.